Richard Bancroft and Elizabethan anti-Puritanism - Collinson, Patrick (Cambridge studies in early modern British history, 2013)
"This major new study is an exploration of the Elizabethan Puritan movement through the eyes of its most determined and relentless opponent, Richard Bancroft, later Archbishop of Canterbury. It analyses his obsession with the perceived threat to the stability of the church and state presented by the advocates of radical presbyterian reform. The book forensically examines Bancroft's polemical tracts and archive of documents and letters, casting important new light on religious politics and culture"--